Communication in the Implementation of the Family Hope Program in Kediri Regency - Janah, Alif Lailatul; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze the implementation of the family of hope program in Tales Village, Ngadiluwih District, Kediri Regency. The type of research used is descriptive qualitative. Data collection techniques were carried out through interviews, observation and documentation. Determination of informants is done by using purposive sampling method. The data analysis technique is done by collecting data, reducing data, presenting data, and drawing conclusions. The results showed that the implementation of the Family Hope Program in Tales Village, Ngadiluwih District, Kediri Regency was quite optimal. Program assistants carry out their duties by continuously coordinating with the village government and conducting regular outreach to beneficiaries. However, there are still obstacles in updating the data which result in delays in disbursement of funds and the appearance of repetitive data and duplicate data.